A hierarchical analysis of structural change and labour productivity convergence across regions, countries and industries within the EU. (3rd April 2019) - Ahmad, Nisar; Naveed, Amjad; Naz, Amber
ABSTRACT: This study explores the effect of structural change on the process of labour productivity convergence at different levels of data aggregations (regions, industries, countries), which is also known as hierarchical convergence analysis in the recent literature. Different forms of structural changes have occurred in the European Union, for instance, variations in the share of employment in different industries, variations in the demand pattern and variations in trade patterns and advancement in technology, which may have an influence on the nature of convergence. Earlier studies on convergence have neglected the effect of the structural change, which may have resulted in different conclusion about the convergence. Based on the results, the study found that the nature of convergence changes after considering the effect of the structural change.